Classes of I-Convergent Double Sequences over n-Normed Spaces - Nazneen Khan (Journal of Function Spaces)
I introduce some new classes of I-convergent double sequences defined by a sequence of moduli over n-normed space. Study of their algebraic and topological properties and some inclusion relations has also been done.